Synthesis of 4-quinolones via triflic anhydride-mediated intramolecular Houben-Hoesch reaction of β-arylamino acrylonitriles. Issue 11 (17th March 2016) - Wu, Chenwei; Huang, Peng; Sun, Zhongqiao; Lin, Mi; Jiang, Yuchun; Tong, Jian; Ge, Chunhua
Abstract: A facile and efficient synthesis of 4-quinolones was described via intramolecular Houben-Hoesch reaction of β-arylamino acrylonitriles mediated by triflic anhydride in N, N -dimethylformamide. Graphical abstract: